The Use of HelloTalk Application in Teaching Speaking - Yorlanda, Fella; Abbas, M. Fadhly Farhy (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
This research was based on the students’ problem in speaking skill at the eleventh grade of Sekolah Menengah Kejuruan (SMK) Negeri 3 Pekanbaru. This research aims at improving the students’ speaking skill. The design of this research was classroom action research. It was conducted in one cycle, which was held for four meetings in one cycle. The subjects of this research were 20 students of class XI Tata Boga 1. The qualitative data were obtained through observations and interviews with the students. The data were in the forms of field notes and interview transcripts. While the quantitative data were obtained from tests. The actions implemented in this research were using HelloTalk application in the teaching and learning process of speaking, implementing chatting with foreigner activities. After conducting this research, the result revealed that the mean score of the students’ speaking performance increased from 61.25 in the preliminary test to 75.00 in the cycle test. The improvement score of the students’ speaking skills was 13.75. In accordance with the scores, the factors that influence the students’ improvement were confident, enjoyable, and highly motivated. The students were more enthusiastic in learning speaking. The students can be actively involved in the learning process of speaking. In conclusion, HelloTalk application can improve the students’ speaking skill.